The Impact of Online Loans on The Community - Kadariah, Siti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The discussion in this study is related to the impact of online lending. Impact on people who do online-based lenajaman. In connection with that, the approach taken is the study and theories of Islamic banking which discusses the impact, online-based loans. This research is a field research (direct research in the field) with a qualitative approach. The data sources used are primary data and secondary data, with data collection techniques through observation, interviews, and documentation.The results showed that the factors that cause people in Sipirok District to make online-based loans, namely the procedure for borrowing money in online-based applications are easier to process and faster disbursement of money. The positive of online-based loans for people in Sipirok District is that the procedure for borrowing money in online-based applications is easier to process and quickly disburse money, and their needs or emergency fund needs can be met quickly. While the negative impact is a deduction of administrative money that reaches 30% of the principal money, and an inhumane way of debt collection to consumers who are in arrears of loan installment payments.